Rosiglitazone Induces Mitochondrial Biogenesis in Differentiated Murine 3T3-L1 and C3H/10T1/2 Adipocytes - James X. Rong; Jean-Louis D. Klein; Yang Qiu; Mi Xie; Jennifer H. Johnson; K. Michelle Waters; Vivian Zhang; Jennifer A. Kashatus; Katja S. Remlinger; Nan Bing; Renae M. Crosby; Tymissha K. Jackson; et al. (PPAR Research)
Growing evidence indicates that PPARγ agonists, including rosiglitazone (RSG), induce adipose mitochondrial biogenesis. By systematically analyzing mitochondrial gene expression in two common murine adipocyte models, the current study aimed to further establish the direct role of RSG and capture temporal changes in gene transcription. Microarray profiling revealed that in fully differentiated 3T3-L1 and C3H/10T1/2 adipocytes treated with RSG or DMSO vehicle for 1, 2, 4, 7, 24, and 48 hrs, RSG overwhelmingly increased mitochondrial gene transcripts time dependently. The timing of the increases was consistent with the cascade of organelle biogenesis, that is, initiated by induction of transcription factor(s), followed by increases in the biosynthesis machinery, and then by increases in functional components. The transcriptional increases were further validated by increased mitochondrial staining, citrate synthase activity, and O2 consumption, and were found to be associated with increased adiponectin secretion. The work provided further insight on the mechanism of PPARγ-induced mitochondrial biogenesis in differentiated adipocytes.